2018
DOI: 10.21037/tau.2018.04.07
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell in urology—are we at the cusp of a new era?

Abstract: Stem cell therapy can potentially disrupt conventional medicine as we practice it today. Stem cells can self-renew and differentiate and by this, repair and in certain conditions regenerate damaged tissue. In the past two decades, there has been significant research into its value in several chronic urological conditions for which conventional therapy is unsatisfactory. Stem cell therapy has been tried on animal models of bladder dysfunction, stress urinary incontinence (SUI), erectile dysfunction and urethral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…There is also a tremendous need for kidney, bladder and urethra regeneration therapies in children with congenital anomalies. Although there are positive experimental data from animal models, and some promising results of early clinical trials of bladder regeneration using a combination of stem cells and biomaterials in children with neurogenic bladder, which is a neurologic defect associated with spina bifida, so far there are no effective stem cell therapies in paediatric urology (10,44,45) .…”
Section: Therapeutic Application Of Mscs In Paediatric Diseasesmentioning
confidence: 99%
“…There is also a tremendous need for kidney, bladder and urethra regeneration therapies in children with congenital anomalies. Although there are positive experimental data from animal models, and some promising results of early clinical trials of bladder regeneration using a combination of stem cells and biomaterials in children with neurogenic bladder, which is a neurologic defect associated with spina bifida, so far there are no effective stem cell therapies in paediatric urology (10,44,45) .…”
Section: Therapeutic Application Of Mscs In Paediatric Diseasesmentioning
confidence: 99%
“…Many preclinical studies have shown that various stem cell therapies for the treatment of CNIED are effective and safe, and stem cell therapy for this purpose has gradually entered the stage of clinical research (Alwaal et al., 2015; Lokeshwar et al., 2020). We and others have found that although stem cell therapy for CNIED has a certain effect, the current therapeutic effect is still weaker than expected, so how to further improve the efficacy of stem cell therapy for CNIED is an important research topic (Caplan & Correa, 2011; Liu et al., 2013; Ouyang et al., 2014; Panda, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the history of regenerative medicine in urology, Atala et al [3,4] showed promising results by implanting a tissue-engineered bladder and ure-thra using autologous cells and scaffolds in humans for the first time. Since then, extensive research has investigated the possibility of using stem cells for therapeutic purposes in various difficult-to-treat urologic diseases such as incontinence, neurogenic bladder (NB), erectile dysfunction, and interstitial cystitis/bladder pain syndrome [5].…”
Section: Introductionmentioning
confidence: 99%